Analysis and Proposed Changes of TIN ORE Processing System on Cutter Suction Dredges into Low Grade to Improve Added Value for The Company - Hutahaean, Benny Pahala; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2013)
Mining technology using Cutter Suction Dredges (KIP) is currently performed by PT Timah (Persero) Tbk. Currently tin ore processing system in KIP produces high grade tin ore (Â±70% Sn). By applying high grade tin ore processing system in KIP, recovery of tin ore is low and associated minerals of tin contained in concentrates secondary jig will be wasted. To change the processing system to be low grade in KIP be enough to negate the sluice box equipment, because the secondary jig produces concentrates of tin ore with low grade levels. System changes tin processing in KIP be low grade, the consequences will transport tin ore to Mineral Processing Plant (PPBT) with a larger amount so that it will add the cost of transportation and processing costs in PPBT. By using production data in 2012, when the operating KIP converted into low grade, the tin is generated by changes in the system amounted to 741,02 tons and will be gained by economic value amounting to Rp. 115.752.676.478,- To implement a system change in tin processing KIP from high grade into low grade to note any factors which are very critical and critical factors. The main requirement of resources is human resources, financial resources, and information technology. Success factor the changes system is atÂ capacity ocean freight, recovery PPBT and management support, so that the system changes in Cutter Suction Dredges tin ore processing of high grade into low grade will succeed.Â Key Words : Cutter Suction Dredges, Mineral Processing Plant, Sluice Box, Tin Ore High Grade, Tin Ore Low Grade,Recovery.